Role of Principal’s Supervision in Improving Teacher’s Competency - Aisyah, Helda Lara (PPSDP International Journal of Education, 2024)
The problem in this study was the learning process not optimal at SMA Negeri 5 Palembang. This article aims to analyze the role of school’s supervision in improving teacher’s competency. In this study I use a qualitative approach. By using data collection techniques in the form of observations, interviews and documentation studies. The results showed that academic supervision of school’s principals can improve teacher’s competency at SMA Negeri 5 Palembang. Academic supervision activities at SMA Negeri 5 Palembang are carried out in several stages, planning, implementation, and evaluation. In improving teacher’s competency, it will be assessed and observed the goals of supervision, the objects of supervision and the techniques that will be used in supervision. Next, the implementation of supervision is carried out by visiting classrooms, observation the activities of teachers and students in the learning process, how to use learning media, and the determination of methods with materials. Finally, the evaluation program carried out on the results of the implementation of supervision. This article recommends to do routinely the supervision in order to get quality teacher’s competency.